2010
DOI: 10.1007/dcr.0b013e3181bdbc32
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Metabolic Syndrome on the Short-Term Outcomes of Colorectal Cancer Surgery

Abstract: Patients with metabolic syndrome had a higher rate of postoperative complication and a longer length of hospital stay than patients without metabolic syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 31 publications
2
23
0
4
Order By: Relevance
“…Moreover, this deleterious influence was also proved for the outcomes of CRC surgery at 30 days, showing a higher rate of postoperative complications and a longer hospital stay in patients classified with the AHA/NHLBI definition of MS. Also in this study from 2009, high blood pressure and high triglyceride levels were as well considered important risk factors for severe complications after CRC surgery, but only the presence of the cluster of metabolic abnormalities that constitute MS was proven to be an independent variable in the multivariate analysis, and not each individual component [13].…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…Moreover, this deleterious influence was also proved for the outcomes of CRC surgery at 30 days, showing a higher rate of postoperative complications and a longer hospital stay in patients classified with the AHA/NHLBI definition of MS. Also in this study from 2009, high blood pressure and high triglyceride levels were as well considered important risk factors for severe complications after CRC surgery, but only the presence of the cluster of metabolic abnormalities that constitute MS was proven to be an independent variable in the multivariate analysis, and not each individual component [13].…”
Section: Introductionmentioning
confidence: 62%
“…In the same year another prospective study from Thailand peremptorily concluded that MS was an independent rick factor for postoperative complications and longer hospital stay in CRC patients submitted to surgery, with a 30 days follow-up [13]. On the other hand, in 2013, a retrospective cohort investigation concluded that MS had no influence on recurrence and overall survival of CRC patients, perhaps explained by the combined effects of elevated blood glucose and hypertension and the protective effect of dyslipidemia, has proven in the same study [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The syndrome diagnoses those people with a dysmetabolic profile, who are, therefore, more likely to develop insulin resistance and consequences of the obese state [87]. There is emerging evidence that the metabolic syndrome is an independent predictor of postoperative complications [93], including cardiac adverse events and acute kidney injury, even after controlling for BMI [94].…”
Section: Insulin Resistance and Type 2 Diabetes Mellitusmentioning
confidence: 99%
“…Эти обстоятельства обусловливают критически низкий уровень качества жизни и являются частой причиной отказа самих па-циентов от операции [20,33].…”
unclassified